Edukasi Pencegahan Dan Penanganan Kegawatdaruratan Pada Penyakit Kronis - Mohammad Arifin Noor; Retno Setyawati; Dwi Nur Aini (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Chronic diseases such as diabetes mellitus, hypertension, heart disease, and asthma require long-term management and vigilance against emergencies that can threaten the patient's safety. Lack of public knowledge regarding the prevention and management of emergencies in chronic diseases often leads to delayed treatment and an increased risk of complications. This Community Service activity aims to improve the community's knowledge and skills in preventing and managing emergencies in chronic diseases. Implementation methods included health education, demonstrations of simple emergency management, interactive discussions, and pre- and post-test evaluations. The results of the activity demonstrated increased public knowledge and preparedness in recognizing danger signs and taking initial emergency measures. This activity is expected to improve the safety and quality of life of people with chronic diseases.